Causal role of the gut microbiome in certain human diseases: a narrative review - Jesse Papenburg; Bertrand Routy; Todd C Lee; Matthew P Cheng; Hao Shi; Cedric P Yansouni; Alexander Lawandi; Connor Prosty; Khaled Katergi; Philip Burnham; Lee Swem (eGastroenterology)
Composed of an elaborate ecosystem of bacteria, fungi, viruses and protozoa residing in the human digestive tract, the gut microbiome influences metabolism, immune modulation, bile acid homeostasis and host defence. Through observational and preclinical data, the gut microbiome has been implicated in the pathogenesis of a spectrum of chronic diseases ranging from psychiatric to gastrointestinal in nature. Until recently, the lack of unequivocal evidence supporting a causal link between gut microbiome and human health outcomes incited controversy regarding its significance. However, recent randomised controlled trial (RCT) evidence in conditions, such as Clostridioides difficile infection, cancer immunotherapy and ulcerative colitis, has supported a causal relationship and has underscored the potential of the microbiome as a therapeutic target. This review delineates the RCT evidence substantiating the potential for a causal relationship between the gut microbiome and human health outcomes, the seminal observational evidence that preceded these RCTs and the remaining knowledge gaps.